Complete mitogenome and phylogenetic significance of Metoecus javanus (Pic, 1913) (Coleoptera: Ripiphoridae) from Southwest China, with notes on morphological traits of adult and immature stages - Li, Jun; Zhou, Zheng; Mao, Chuyang; Pan, Zhao; Yao, Yuhao; He, Jinwu; Lin, Yan; Dong, Zhiwei; Liu, Guichun; Zhao, Ruoping; Wang, Wen; Li, Xueyan (Zootaxa, 2022)
Wedge-shaped beetles (Ripiphoridae) not only exhibit enigmatic morphological and biological traits but also disputable phylogenetic positions. At present, however, genetic information regarding this family remains limited. In this study, we report on the complete mitogenome of one ripiphorid beetle, Metoecus javanus (Pic, 1913), from Southwest China, as well as its different developmental stages, populations, and morphological variability. The complete mitogenome of M. javanus was 16 109 bp in length, containing 13 protein-coding genes (PCGs), two ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes, and a noncoding control region. Of the 37 genes, 23 were located on the majority strand (J-strand) and 14 were located on the minority strand (N-strand). All PCGs started with “ATN” (N represents A, T, G, and C), and terminated with “TAA”, except for NAD1 with “TAG” and COX2 with a single “T”. The five most used codons in the PCGs were UUA(L), UCU(S2), CCU(P), UCA(S2), and GGA(G), indicating a strong bias toward A + T-rich codons. All 22 tRNAs showed typical cloverleaf structures, except trnS1, which lacked a dihydrouridine (DHU) stem. The control region contained five types of tandem repeats, with the repeat units ranging from 17 to 24 bp. Phylogenetic analysis of the concatenated set of 13 PCGs and two rRNAs (rrnL and rrnS) of M. javanus and 17 other Tenebrionoidea species indicated that M. javanus did not cluster with Pelecotoma fennica (Ripiphoridae: Pelecotominae), another wedge-shaped beetle, but was located at the base of the Mordellidae + P. fennica clade. This reconstruction supported the paraphyly of Ripiphoridae with respect to Mordellidae. Using the mitogenome COX1 data, wedge-shaped beetles from different stages (male adult, female adult, and pupa), different geographical populations (Nujiang and Lincang), and different wasp hosts (Vespidae: Vespa velutina Lepeletier, 1836 and Vespa bicolor Fabricius, 1787) were identified as a same species (i.e., M. javanus). Based on morphological observations of all specimens, we identified and described variability in the adult pronotum, male genitalia, and pupa of M. javanus. The present results provide important genetic and morphological information for further investigations on the phylogenetic position of Ripiphoridae and its evolutionary diversity.